PENGGUNAAN METODE PROBLEM BASE LEARNING (PBL) PADA MATA KULIAH STATISTIKA NONPARAMETRIK - Suciptawati, N.L.P; Asih, M. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
The purpose of community service is to improve the ability of students to understand subjects Nonparametric Statistics, using the approach of problem base learning (PBL). PBL is an instructional method that challenges students to "learn and learn", in collaboration with the group to find solutions to real problems. In the process of learning the students were divided into 7 groups. Each group looking for problems in the real world that they can accomplish with Nonparametric Statistics method, then the results were presented to the class. The effectiveness of teaching methods was assessed by giving Pree test and post-test on students. The result of pre-test and post-test were tested using the Wilcoxon signed rank test with significansi level of 5%. Wilcoxon signed rank test results show that the method PBL effectively improve students' scores.